Delayed deterioration in patients with traumatic frontal contusions. Issue 3 (March 1989) - Statham, P F; Johnston, R A; Macpherson, P
Abstract : The clinical course of 18 head injured patients in whom CT had shown frontal contusions without diffuse brain injury or intracranial haematoma was reviewed. All 10 patients with unilateral frontal contusion made a good recovery. Only two of five patients with limited bilateral frontal contusions made a good recovery. Two of three patients with extensive bilateral frontal contusions deteriorated more than 24 hours after injury, and one died. Delayed deterioration is an important complication of extensive traumatic bifrontal contusions.